SPIRITUAL INTELLIGENCE AND LIFESTYLE ON PERSONAL FINANCIAL MANAGEMENT OF OVERSEAS STUDENTS STUDYING IN MAKASSAR - Awanda Lestari Buia; Wa Ode Rayyani; Amelia Rezki Septiani Amin (CV. AFDIFAL MAJU BERKAH, 2024)
The purpose of this study was to determine the effect of spiritual intelligence and lifestyle on personal financial management of overseas students studying in Makassar. The type of data used in this research is quantitative data taken from migrant students majoring in Management, Faculty of Economics and Business, Muhammadiyah University, Makassar. In this research, the data source used in data collection is primary data through distributing questionnaires. The research instrument used in this research uses the Likert scale method. Based on the results of data research using statistical calculations through the SPSS application regarding the influence of spiritual intelligence and lifestyle on the personal financial management of migrant students studying in Makassar which has been discussed, it shows that the spiritual intelligence variable has a positive and significant influence on personal financial management and the lifestyle variable also has positive and significant influence on personal financial management. Spiritual intelligence will encourage high levels of personal financial management in students. Students must train their spiritual intelligence and avoid excessive lifestyles in order to improve their personal financial management.